Adopting GIS to Enhance Alexandrian Urban Cultural Heritage: The Case of Alexandria, Egypt - Othman, Esraa; Abdelghany, Sarah; Farghaly, Tarek (Alanya Üniversitesi, 2025)
Heritage conservation in Alexandria demands integrative, data-driven approaches that reconcile preservation efforts with satisfactory visitor access. This study investigates how Geographic Information Systems (GIS) can document, evaluate, and spatially optimise the city’s cultural heritage. A four-stage framework was applied: (1) compiling a multi-source geodatabase of 294 heritage assets in addition to transport nodes; (2) digitising attributes for value scoring based on five National Organisation of Urban Harmony (NOUH) criteria; (3) conducting spatial analytics—hot-spot, nearest-neighbour, buffer, and network analysis—together with a six-parameter walkability index; and (4) translating findings into policy-relevant interventions and interactive web maps. Results reveal pronounced clustering in the historic downtown;however 83 high-value assets lie outside a 400 m walk from transit, notably in Foad Street, Kafr-Abdo, and Ancient Catacombs sub-areas. Proposed measures—two bus-stop extensions, and one new tram halt would reduce unserved sites to 8.5 per cent. Six optimised cultural routes cut average walking time within heritage clusters to maximise exposure to unique assets. A dashboard links routes, heritage metadata, and multimodal travel options as well as enabling user-defined preference customisation. The research demonstrates GIS’s capacity to integrate qualitative heritage evaluation with quantitative mobility analytics, offering a transferable model for sustainable, economically beneficial urban heritage management.